Implementation of the HIRADC Method in Risk Analysis of Diaphragm Wall Work Projects - Kholida, Lily; Sumarmi, Sumarmi (PT Mattawang Mediatama Solution, 2023)
The decreasing land area in big cities makes construction progress develop not only vertically upwards, but also downwards. This is done to optimize the land use. One of the things is the construction of a basement as a parking lot, storage space, and other functions to be neatly organized and safe. There are numerous employment risks in basement work that can result in building failures that hinder other construction activity. This research was conducted at a company that focuses on the business of guitar manufacturing, retaining walls, and soil improvement in three high-rise building construction projects that are currently building, and experiencing difficulties in identifying the main risks in diaphragm wall work. The soil conditions are different at each project site, which is not the same as the superstructure work. It is more typical and the quite large project value reaching more than 100 billion than can be classified as a major construction project. The risks that will be encountered in its implementation will also be large. The steps involved in the research were risk identification, risk qualitative analysis, and extreme risk response planning by experts. There were sixty-four (64) identified risks relevant to the project construction phase, classified into eleven categories. The risk was then simulated to obtain high risk and control risk plans that would be carried out when the high risk occurs. There are four high risks, namely the damaged or non-compliant construction materials, inaccurate specifications, delays in the execution of constructor work, and slope failure during excavation.